Adherence to Iron-Folate Supplementation and Associated Factors among Pastoralist's Pregnant Women in Burji Districts, Segen Area People's Zone, Southern Ethiopia: Community-Based Cross-Sectional Study. (31st December 2018) - Boti, Negussie; Bekele, Tezera; Godana, Wanzahun; Getahun, Eskeziyaw; Gebremeskel, Feleke; Tsegaye, Behailu; Oumer, Bilcha
Abstract : Background . Iron deficiency anemia among pregnant women is one of the most common public health problems in developing country particularly in Ethiopia. Iron/folic acid supplementation with optimal adherence is the main cost-effective strategy for prevention and control of iron deficiency anemia in pregnant women. However, level of adherence to iron/folic acid supplementation and its associated factors were not well identified in study area. Therefore, the aim of this study was to determine the level of adherence to iron/folic acid supplementation and associated factors among pregnant women in Burji Districts, southern Ethiopia. Methods . A community-based cross-sectional study was conducted among 317 pregnant women in Burji Districts from March to April 2017 using interviewer administered questionnaires. Data were entered into Epi Info 3.5.1 and exported to SPSS version 20.0 for analysis. Binary and multivariable logistic regression was used to identify factors associated with iron/folic acid supplementation. Adjusted odds ratio (AOR) with 95% confidence interval (CI) and p-value <0.05 were used to declare statistical significance. Results . Among women participating in the study, 163(51.4%) were adherent to iron/folate acid supplementation. Factors significantly associated with adherence to iron and folic acid supplementation were maternal educational status (AOR: 2.47, 95% CI: 1.13-4.97), early registration for ANC (AOR: 2.49, 95% CI: 1.45 – 4.27), history of anemia during current pregnancy (AOR: 2.02, 95% CI: 1.09-3.72), and knowledge about iron and folic acid supplementation (AOR: 1.96, 95% CI: 1.02-3.76). Forgetfulness and fear of side effects were among the leading reasons of pregnant women for nonadherence to iron and folic acid supplementation. Conclusions . This study revealed that adherence to iron /folic acid supplementation was found to be 51.4%. Maternal educational status, early registration for ANC, history of anemia during current pregnancy, and knowledge about iron and folic acid supplementation were significant factors associated with adherence to iron/folic acid supplementation among pastoralist's pregnant women. Therefore, anemia prevention strategy should include strengthening giving awareness, counseling, strengthening community health education, and participation in health programs which are necessary to improve the uptake of iron/folic acid supplements.